Achieving ultrahigh power factor in n-type Ag2Se thin films by carrier engineering. (March 2022) - Zheng, Zhuang-Hao; Zhang, Dong-Liang; Niu, Jun-Yu; Shi, Xiao-Lei; Chen, Tian-Bao; Chen, Yun-Fei; Li, Fu; Liang, Guang-Xing; Chen, Yue-Xing; Fan, Ping; Chen, Zhi-Gang
Abstract: Ag2 Se-based thermoelectric materials are attracting great attention because of their potential in fabricating high-performance miniature and wearable electronics. Here, an advanced thermal co-evaporation method is employed to fabricate high-performance Ag2 Se thin films with controllable compositions. The atomic ratio Ag/Se of 2.06 can tune the carrier concentration to 1.4 × 10 19  cm −3, leading to a power factor of 6.27 μW cm −1 K 2 at room temperature. As well, an annealing process further improves the electrical transport properties by increasing the carrier mobility while maintaining the carrier concentration. Microstructure analysis indicates that annealing can reduce dislocation defect density and Ag vacancy concentration, contributing to a high Seebeck coefficient, finally resulting in a high power factor of 20.51 μWcm −1 K −2  at 393 K. Moreover, a thermoelectric device composed of 18 legs is fabricated by using the optimized Ag2 Se thin film, which presents a maximum output voltage and power of ∼1.7 mV and ∼22 nW at the temperature difference of 50 K. These results demonstrate that a combination of compositional optimization and annealing condition manipulation is effective to boost the thermoelectric performance of Ag2 Se thin films, showing great potentials in applying for wearable electronics. Graphical abstract: Image 1 Highlights: High performance Ag2 Se based thin films are prepared via a simple co-evaporation method. Electrical transport properties are optimized via an annealing process. The best power factor of 20.51 μWcm −1 K −2  at 393 K is achieved for the Ag2 Se thin film. The fabricated device can generate a stable output voltage around 0.3 mV under intermittent laser irradiation.